The Dangers of Technological Disinformation in William Gibson's Neuromancer - Muhammad Fadlillah Ashari (Fakultas Ilmu Budaya, 2026)
This research analyses technological disinformation in Neuromancer (1984) by William Gibson. This novel depicts a world with a highly advanced technology that is misused for the sake of personal interest, with technological disinformation as the repeating theme The research sims to identify the narrative structure of technology-based disinformation in the novel, analyse the socio-historical context behind the text, and reveal the worldview that is embedded in the text. The method used is qualitative with the dialectical theory of genetic structuralism by Lucien Goldmann through comprehension and explanation. The results of the research show that technology disinformation in Neuromancer is a hyperbobe reflection of technology anxiety and the concerns of surveillance and technology that is rapidly developing in the United States in the era ra of the Cold War, specifically between the late 1970s suntil the early 1980s, the tinie when computers and technological advancement triggered enthusisun as well as public unease. This research concludes that Neuromancer is not merely a work of fiction, but rather a structured expression of the social group of the author of the novel, namely the tech-aware youth of the growing technological era that responds to the new social reality that is developing without the existence of adequate supervision.
Finalisasi Maya_08 Juli 2026
Keywords: Dystopia; Genetic Structuralism; Worldview; Neuromancer; Cold War